Desigualdades de Penrose e um teorema da massa positiva para buracos negros carregados - Lozório, Weslley Marinho (2014)
We present Penrose-type inequalities and a positive mass theorem to charged black roles, ie, initial data for time-symmetric solutions of the Einstein-Maxwell equations, which can be isometrically immersed in Euclidean space as graphics. The statements use an integral formula for the ADM mass of such hypersurfaces and the inverse mean curvature flow.